Overeducation in the Swiss labour market: Does anything go wrong? - Aniela Wirz; Erdal Atukeren (ETH Zurich, KOF Swiss Economic Institute, 2004)
We examine the determinants of overeducation in Switzerland - an economy generally characterised by excess qualified labor demand. We define those who are overeducated more precisely, and include in our sample only those who work in occupations relating to their educational background. Failing to make this adjustment might have blurred the results of earlier studies. Our analyses show that overeducation in Switzerland cannot be explained by rigidities limiting the adjustments of supply and demand in the labor market. Hence, the Swiss labor market must in general be considered as efficient. Unobserved heterogeneity should indeed account for the phenomenon of overeducation.
Keywords: J16; J24; J61; 330; Overeducation; Swiss labor market; Education policy; Qualifikation; Arbeitsmarkt; Bildungspolitik; Schweiz